PELUANG DAN TANTANGAN PEMBERLAKUAN HUKUM PIDANA ISLAM DI INDONESIA - Irfan Islami; Ely Alawiyah Jufri (JOURNAL OF LAW AND NATION, 2024)
Islamic law is one of the sources of national law in the Republic of Indonesia which has been in effect since the time when the Islamic kingdom was established in the archipelago. The Islamic law that applies in Indonesia has so far been dominated by civil law, especially family law and sharia economics. Islamic criminal law is not enforced in the national legal order, but the efforts and encouragement of some Muslim groups are still advocating for the implementation of Islamic criminal law in Indonesia. This research examines in more depth the opportunities and challenges of implementing Islamic criminal law in Indonesia. This research was conducted using qualitative methods using normative research. The implementation of Islamic criminal law in Indonesia is not a new ideal echoed by some Muslim groups, but has existed since the discussion of the foundation of the Republic of Indonesia in 1945. The implementation of Islamic criminal law in Indonesia has only recently been implemented in Aceh Province, which is contained in regional regulations. Aceh Province (Qanun).